Upaya Peningkatan Imunitas Tubuh Masyarakat Kampung Rancasalak-Cimaung dengan Edukasi PHBS dan Pemanfaatan Toga - Dadang Juanda; Muhamad Reza Pahlevi; Nita Selifiana; Ika Kurnia Sukmawati; Widhya Aligita (Warta Pengabdian Andalas, 2024)
Body immunity for a worker major role in providing optimal performance in their work. Good immunity can be obtained by implementing PHBS and consuming herbs which are known to increase immunity. This activity is carried out in order to improve the quality of health in order to improve the quality of people in carrying out their activities, especially work. Community service activities will be carried out on November 13, 2023 to November 20, 2023. Activities include promotional efforts such as providing education about Perilaku Hidup Bersih dan Sehat (PHBS) and medicinal plants to increase immunity, moreover providing tutorials on how to process instant granules from TOGA. The results of the pre & post-test scores provide an illustration that there is an increase in understanding of PHBS and TOGA. It is hoped that the information provided will have a positive impact on the health of the UMKM cracker and chips workers in Kampung Rancasalak.